Review: Utilization of Nuclear Technology in Agriculture and Food Sector - Astuti, Retno Dwi; Handayani, Nita (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The development of nuclear technology is beneficial for many sectors including farming, health, industry, hydrology, archeology, mining, and agriculture and food. One of the interesting thing to be discussed is utilization of nuclear technology in agriculture and food sector. These sectors are crucial and closely related to the fulfillment of human life needs. This article discussed the use of nuclear technology in agriculture and food. The implementation of nuclear technology in agriculture and food could be found in several things, those are in mutations for plant breeding using gamma irradiation technique, fertilization efficiency using tracer technique, plant pests control using the sterile insect technique (TSM), and food or crops preservation using irradiation technique. By maximizing the utilization of nuclear technology, it is expected that it can increase productivity in the agriculture and food sectors.